Topology-optimized hybrid solid-lattice structures for efficient mechanical performance. (February 2021) - Teimouri, Mohsen; Mahbod, Mahshid; Asgari, Masoud
Abstract: Considering topology optimization as a widely used tool in the design of lightweight structures and lattice structures as an emerging solution toward mechanically efficient structures, their contribution to each other can be regarded as a promising procedure in the design process toward next-generation lightweight structures. This study aims to develop new hybrid solid-lattice structures consisting of different strut-based lattice wireframes assembled to topology optimized solid structures which are resulted from the Bidirectional Evolutionary Structural Optimization (BESO) method. In this regard, the optimization procedure and the lattice generation process are discussed in detail and implemented on the Messerschmitt-Bolkow-Blohm (MBB) beam. Then, to explore the mechanical performance of the newly proposed structures, stiffness, modal, and quasi-static finite element analyses (FEA) are conducted and results are compared to the classic solid structures and the lattice wireframes corresponding performance. An improved mechanical performance regarding stiffness, buckling failure load and energy absorption is seen in novel hybrid solid-lattice structures in comparison with the pure solid structures and the lattice wireframes while the effect of different unit cells can also be tracked. Moreover, regarding frequency analysis, although structural mass is considerably increased in the hybrid structures; the fundamental frequency is slightly reduced.